Systematics and Phylogenetics of Indo-Pacific Luciolinae Fireflies (Coleoptera: Lampyridae) and the Description of new Genera - Ballantyne, Lesley A.; Lambkin, Christine L. (Zootaxa, 2013)
This revision completes a taxonomic survey of fireflies (Coleoptera: Lampyridae) in the area encompassed by Australia, the Republic of Palau, Federated States of Micronesia, Papua New Guinea, Indonesia (West Irian/Papua), Solomon Islands, New Caledonia, Vanuatu and Fiji. It finalises the taxonomic issues arising from the 1969–70 voyage of the scientific vessel Alpha Helix to New Guinea. The firefly fauna of this area is exclusively Luciolinae. The scope of the revision was extended to include all known Luciolinae genera and certain species from SE Asia, and a phylogenetic analysis of 436 morphological characters of males, females, and associated larvae includes 142 Luciolinae species (Ballantyne & Lambkin 2009, and Fu et al. 2012a). The phylogenetic analyses infer four major groups within the Luciolinae. The monotypic Missimia Ballantyne is sister to all remaining Luciolinae and forms a grade to Aquatica Fu etBallantyne. The large clade of Curtos Motschulsky, Photuroluciola Pic, Colophotia Motschulsky, Poluninius gen. nov., Pyrophanes Olivier, Pteroptyx s. str. Olivier, Medeopteryx gen. nov., Trisinuata gen. nov., and Australoluciola gen. nov.forms a grade to the clade of Luciola s. str. Laporte (including Bourgeoisia Olivier). The monotypic Emeia Fu et al.forms a grade with a clade of Luciola and Pygoluciola Wittmer, sister to a large clade of Convexa Ballantyne, Pacifica gen. nov., Magnalata Ballantyne, Lloydiella Ballantyne, Asymmetricata Ballantyne, Pygatyphella s. str. Ballantyne, Atyphella Olliff, Aquilonia Ballantyne, and Gilvainsula Ballantyne. Luciola is paraphyletic, found in up to six clades across the tree. Together with Luciola, Magnalata, Aquilonia, and Gilvainsula render Atyphella paraphyletic. The new genera described here are all monophyletic and supported in the phylogenetic analyses that also provide evidence for the inclusion of taxa within them. Twenty-three genera including five new ones, and ten new species, are recognised and keys are presented for the males and females. Certain females are characterised by the nature of their bursa plates.Australoluciola gen. nov. is proposed for ten species from Australia and New Guinea, seven transferred from Luciola and three new, with species keyed from males, all of which have an entire light organ in ventrite 7. Aus. anthracina (Olivier), Aus. aspera (Olivier), Aus. australis (F.), Aus. flavicollis (MacLeay), Aus. foveicollis (Olivier), Aus. nigra (Olivier) and Aus. orapallida (Ballantyne) are transferred from Luciola with males assigned to Aus. aspera(Olivier), and a lectotype designated for Luciola foveicollis Olivier; Aus. baduria sp. nov., Aus. fuscamagna sp. nov.,Aus. fuscaparva sp. nov., Aus. japenensis sp. nov. and Aus. pharusaurea sp. nov. are described. Females of Aus. australis and Aus. flavicollis have two pairs of wide bursa plates.The bent-winged fireflies of New Guinea and Australia are removed from Pteroptyx Olivier and assigned to Medeopteryx gen. nov. and Trisinuata gen. nov. Medeopteryx gen. nov. is erected for 17 species including two new; all have ventrite 7 with an entire light organ, trisinuate posterior margin and short posterolateral projections; the following 14 species in which males have deflexed elytral apices are transferred from Pteroptyx Olivier: M. amilae (Satô), M. antennata (Olivier), M. corusca (Ballantyne), M. cribellata (Olivier), M. effulgens (Ballantyne), M. elucens (Ballantyne), M. flagrans (Ballantyne), M. fulminea (Ballantyne), M. hanedai (Ballantyne), M. platygaster (Lea), M. similisantennata(Ballantyne), M. sublustris (Ballantyne), M. tarsalis (Olivier), and M. torricelliensis (Ballantyne). M. clipeata sp. nov. is described. Two species without deflexed elytral apices include M. pupilla (Olivier) which is transferred from Luciola, and M. similispupillae sp. nov. A Lectotype is designated for Luciola pupilla (Olivier). Females of M. corusca(Ballantyne), M. cribellata (Olivier), M. effulgens (Ballantyne), and M. similispupillae sp. nov. have two pairs of wide bursa plates. The second genus including species in which the males have deflexed elytral apices is Trisinuata gen. nov., where all males have light organ in ventrite 7 bipartite and posterolateral projections expanded; it is proposed for eight New Guinean species: T. microthorax (Olivier), T. minor (Ballantyne), T. papuae (McDermott) and T. similispapuae(Ballantyne) are transferred from Pteroptyx Olivier, T. papuana (Olivier) previously known only from a female, has males associated and is transferred from Luciola, and T. caudabifurca sp. nov., T. dimidiata sp. nov. and T. apicula sp. nov. are described. Females of T. similispapuae (Ballantyne) have two pairs of wide bursa plates.Luciola s. str. is defined by scoring the type species L. italica (L), Bourgeoisia Olivier and Lampyroidea (based on its type species syriaca Costa) both of which are submerged into Luciola; Luciola s. str is addressed here from four Pacific Island species: L. hypocrita Olivier, L. antipodum Bourgeois both transferred from Bourgeoisia; L. aquilaclarasp. nov. and L. oculofissa sp. nov. are described. L. oculofissa sp. nov. is the only Luciolinae male known to lack light organs. Females of L. italica and L. hypocrita lack bursa plates.Pacifica gen. nov. is proposed for five species from the Solomon Islands transferred from Pygatyphella(Ballantyne), and which the phylogenetic analysis shows to be distinctive viz. P. limbatifusca (Ballantyne), P. limbatipennis (Pic), P. plagiata (Blanchard), P. russellia (Ballantyne), and P. salomonis (Olivier).A monotypic genus Poluninius gen. nov. is proposed for Pol. selangoriensis sp. nov. from Selangor, Malaysia. The genera Colophotia, Pteroptyx, Pyrophanes, and Pygoluciola are treated in an abbreviated fashion with generic diagnoses, lists of, and keys to, species. Pteroptyx bearni Olivier and P. tener Olivier are characterised from type specimens and female bursae and P. similis Ballantyne is synonymised with P. bearni. Luciola semilimbata Olivier is transferred toPyrophanes, and Luciola cowleyi Blackburn to Pygoluciola. The following species are treated as species incertae sedis: L. melancholica Olivier, L. ruficollis Guérin-Ménéville. The New Guinean records of Luciola tenuicornis Olivier, L. timida Olivier and Photinus cinctellus Motschulsky are suspect. Fifteen of the species treated here are recognised by flashing patterns. The functions of the terminal abdominal modifications, origins of the Australopacific firefly fauna, and use of female and larval characters in interpretations of relationships are considered.